Social Reflection in Novel Tenki No Ko by Makoto Shinkai: The Study of Marxisy Literary Sociology - Ayu Putri Seruni (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The purpose of this research is to find out the social reflection in the world-famous novel, Tenki no Ko by Makoto Shinkai. This novel has a good message in its presentation and in the research it discusses in terms of social reflection on the situation of Japanese society in Tokyo. Characters developed from the lower society who try to resolve conflicts in real life with a touch of fantasy series. The presentation that is packaged is very interesting, attracting readers from this novel. Therefore, the discussion in this study regarding social reflection in the novel Tenki no Ko by Makoto Shinkai shows social reality, the suffering of the lower class, class and society, has siding with the lower society, propaganda against the rulers. The social reflection in this novel can reflect the lives of young people running away from home struggling with the rigors of life in the capital city with various social problems. Keyword: Social reflection, Novels, tenki no ko, sociology of Marxist literature